Novelty and Convergence in Adaptation to Whole Genome Duplication. (30th March 2021) - Bohutínská, Magdalena; Alston, Mark; Monnahan, Patrick; Mandáková, Terezie; Bray, Sian; Paajanen, Pirita; Kolář, Filip; Yant, Levi
Abstract: Whole genome duplication (WGD) can promote adaptation but is disruptive to conserved processes, especially meiosis. Studies in Arabidopsis arenosa revealed a coordinated evolutionary response to WGD involving interacting proteins controlling meiotic crossovers, which are minimized in an autotetraploid (within-species polyploid) to avoid missegregation. Here, we test whether this surprising flexibility of a conserved essential process, meiosis, is recapitulated in an independent WGD system, Cardamine amara, 17 My diverged from A. arenosa . We assess meiotic stability and perform population-based scans for positive selection, contrasting the genomic response to WGD in C. amara with that of A. arenosa . We found in C. amara the strongest selection signals at genes with predicted functions thought important to adaptation to WGD: meiosis, chromosome remodeling, cell cycle, and ion transport. However, genomic responses to WGD in the two species differ: minimal ortholog-level convergence emerged, with none of the meiosis genes found in A. arenosa exhibiting strong signal in C. amara . This is consistent with our observations of lower meiotic stability and occasional clonal spreading in diploid C. amara, suggesting that nascent C. amara autotetraploid lineages were preadapted by their diploid lifestyle to survive while enduring reduced meiotic fidelity. However, in contrast to a lack of ortholog convergence, we see process-level and network convergence in DNA management, chromosome organization, stress signaling, and ion homeostasis processes. This gives the first insight into the salient adaptations required to meet the challenges of a WGD state and shows that autopolyploids can utilize multiple evolutionary trajectories to adapt to WGD.